Key challenges of new and small virtual team - Räsänen, Tomi (2007)
The purpose of this thesis is to study the factors must be noticed when building a new and small virtual team. These virtual teams are groups of people who work together without the boundaries of time or space using technology (Lipnack & Stamps 2000, 18). The main goal is to study in detail some of the common challenges faced when working with the small virtual teams, especially in the early stages of team development. With this study and the results of it, the reader is aware of the challenges of virtual teams and the differences and similarities between traditional and virtual teams. In addition the reader knows also some factors that must be noticed when a new small virtual team is supposed to be created. Based on a literature about the subject a framework for the challenges of the virtual teams is created. With a case study the framework is studied in more detail.